HUBUNGAN ANTARA JARAK KEHAMILAN DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH (BBLR) DI RSU MUHAMMADIYAH PONOROGO - Setiawan, Sinta Ayu; Hardiani, Merico Putri (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2018)
ABSTRACT Â The distance a large influential pregnancy which can cause low birth weight incidence, risks of pregnancy the pregnancy at a distance of less than two years after giving birth to low birth weight babies usually arise due to the onset of the reproductive organs have not been returned to its original form, the uterus is not yet mature enough to bear the burden of pregnancy again. The impacts that occurred in place research rsu muhammadiyah ponorogo january until december 2015 of 32 infants with a low birth weight baby died with complications 1 failed the breath after 2 days of treatment. The purpose of this research is to know the relation between the distance of the pregnancy with low birth weight (LBW) in Parturition Room Siti Walidah Muhammadiyah Hospital Ponorogo. This type of research using the method of analytic survey, with a retrospective apporach. Population and sample in this research are all mothers who give birth to babies with low birth weight in Parturition Room Siti Walidah Muhammadiyah Hospital Ponorogo 2015 as many as 32. This research was conducted in January 2017. To view the relationship between two variables is performed with spearman rank test with a significance level of 0,05. From the data of 32 respondents examined maternal distance of pregnancy found that most 24 respondents (75%) have distance of 2-10 years of pregnancy, the incidence of low birth weight was found almost entirely 29 respondents (90,625%) had low birth weight. Based on statistical test showed that p value = 0,000 so the value p<a 0,05 so it is state H0 rejected H1 accepted wich means significant, while correlation coefficient = 0,620** which means the level of closeness is very strong. Based on the results of the study, the researchers suggest is expected to serve as a material consideration, entries, and information for decision making in health care improvement efforts in terms of the importance of spacing pregnancies for expectant mothers. Â Keywords: Pregnancy, Distance, BBLR